Exhausted and Senescent T Cells at the Maternal-Fetal Interface in Preterm and Term Labor. (23rd May 2019) - Slutsky, Rebecca; Romero, Roberto; Xu, Yi; Galaz, Jose; Miller, Derek; Done, Bogdan; Tarca, Adi L.; Gregor, Sabrina; Hassan, Sonia S.; Leng, Yaozhu; Gomez-Lopez, Nardhy
Abstract : Successful pregnancy requires a tightly-regulated equilibrium of immune cell interactions at the maternal-fetal interface (i.e., the decidual tissues), which plays a central role in the inflammatory process of labor. Most of the innate immune cells in this compartment have been well characterized; however, adaptive immune cells are still under investigation. Herein, we performed immunophenotyping of the decidua basalis and decidua parietalis to determine whether exhausted and senescent T cells are present at the maternal-fetal interface and whether the presence of pathological (i.e., preterm) or physiological (i.e., term) labor and/or placental inflammation alter such adaptive immune cells. In addition, decidual exhausted T cells were sorted to test their functional status. We found that (1) exhausted and senescent T cells were present at the maternal-fetal interface and predominantly expressed an effector memory phenotype, (2) exhausted CD4 + T cells increased in the decidua parietalis as gestational age progressed, (3) exhausted CD4 + and CD8 + T cells decreased in the decidua basalis of women who underwent labor at term compared to those without labor, (4) exhausted CD4 + T cells declined with the presence of placental inflammation in the decidua basalis of women with preterm labor, (5) exhausted CD8 + T cells decreased with the presence of placental inflammation in the decidua basalis of women who underwent labor at term, (6) both senescent CD4 + and CD8 + T cells declined with the presence of placental inflammation in the decidua basalis of women who underwent preterm labor, and (7) decidual exhausted T cells produced IFN γ and TNF α upon in vitro stimulation. Collectively, these findings indicate that exhausted and senescent T cells are present at the human maternal-fetal interface and undergo alterations in a subset of women either with labor at term or preterm labor and placental inflammation. Importantly, decidual T cell function can be restored upon stimulation.